P2Y12 hyporesponse (PRU>200) is not associated with increased thromboembolic complications in anterior circulation Pipeline. (6th September 2016) - Bender, Matthew T; Lin, Li-Mei; Colby, Geoffrey P; Lubelski, Daniel; Huang, Judy; Tamargo, Rafael J; Coon, Alexander L
Abstract : Introduction: Recent reports suggest that thromboembolic complications are associated with Pipeline embolization device (PED) placement cluster in P2Y12 hyporesponders. Objective: To evaluate the role of P2Y12 hyporesponse in PED placement by retrospectively reviewing a single-center series of patients. Methods: We retrospectively reviewed an institutional review board-approved database of patients with an aneurysm at a single institution and identified all patients with a measured P2Y12 reaction unit (PRU)>200 who had undergone anterior circulation PED placement. Events such as transient ischemic attack, stroke, and hemorrhage were identified as well as demographic and procedural details. Results: Fifty-two patients with a PRU >200 had undergone anterior circulation PED placement. Four patients had prior subarachnoid hemorrhage (SAH) (8%) and 11 aneurysms (21%) had been previously treated. The average aneurysm size was 7.6 mm (±6.2). PED thrombosis occurred intraprocedurally in three patients, none of whom developed neurological deficits after abciximab administration. Treatment of all patients was successful and 48 procedures (92%) had no complications. One patient had a major stroke (2%) with permanent hemiparesis. There were three minor complications (6%): one minor stroke with a visual field cut, one 10 cc intracranial hemorrhage with transient left lower extremity weakness, and one transient neurological deficit not verified by imaging. No deaths or cases of SAH occurred. Conclusions: P2Y12 hyporesponse (PRU>200) is not associated with increased periprocedural complications in a contemporary series of patients undergoing anterior circulation PED placement. Titration of antiplatelet medications to P2Y12 >200 remains unindicated and may increase the risk of hemorrhagic complications.